(untitled) (Research, Society and Development, 2020)
In Central Auditory Processing Disorder (CAPD), also called Central Auditory Dysfunction or Auditory Processing Disorder, the child listens, but does not understand well what is spoken, and this is characterized by the difficulty of decoding sounds (ability to understand the who heard); coding (ability to build information based on what you heard); prosody (ability to pronounce words correctly); and auditory memory. This theoretical work aims to analyze the importance of early identification in the diagnosis of central auditory processing disorder and its interferences in learning from the perspective of psychopedagogy. The results obtained with this research showed that the knowledge and involvement of psychopedagogy about CAPD needs to be better disseminated in the school and family environment. the affected skills in a playful way, mediating the subject in his learning process. Finally, it is clear that scientific studies on CAPD in the educational field lack researchers who have a deep understanding within the psychopedagogical context, since there are few findings in the literature beyond speech therapy. There are many theoretical and practical foundations for support in the clinical area. It is believed that psychopedagogy, in the appropriation of knowledge about CAPD, may offer strategies that will help psychopedagogical interventions to individuals with central auditory processing disorder in a satisfactory and efficient way.